Electrophysiological Evidence of a Delay in the Visual Recognition Process in Young Children - Barriga-Paulino, Catarina I.; Rodríguez-Martínez, Elena I.; Rojas-Benjumea, Mª Ángeles; Gómez González, Carlos M. (Frontiers in Human Neuroscience, 2015)
The present study analyzes the development of the visual recognition processing of the relevant stimulus in a Delayed Match-To-Sample task during the matching phase. To do so, Electroencephalograms of 170 subjects between 6 and 26 years old were recorded. Behavioral responses and Event Related Potentials induced by the stimuli were obtained. Reaction times and errors, mainly omissions, were inversely related to age. The Event Related Potentials analysis showed a parietal negativity in the P7 and P8 electrodes when the relevant stimulus was presented in the contralateral site. This negativity resulting from the recognition and selection of the relevant stimulus was present in all age groups. However, the youngest children showed an extended latency in the recognition process. The results suggest that children and adults use similar processes to recognize the item maintained in visual short-term memory, but children need more time to successfully recognize the memorized item.